2016
DOI: 10.1016/j.redox.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of GSTA4-4 results in increased mitochondrial post-translational modification of proteins by reactive aldehydes following chronic ethanol consumption in mice

Abstract: Chronic alcohol consumption induces hepatic oxidative stress resulting in production of highly reactive electrophilic α/β-unsaturated aldehydes that have the potential to modify proteins. A primary mechanism of reactive aldehyde detoxification by hepatocytes is through GSTA4-driven enzymatic conjugation with GSH. Given reports that oxidative stress initiates GSTA4 translocation to the mitochondria, we hypothesized that increased hepatocellular damage in ethanol (EtOH)-fed GSTA4−/− mice is due to enhanced mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 54 publications
0
37
0
2
Order By: Relevance
“…In addition, proteomic analysis of lysates from aged murine liver (89), Alzheimer's disease brain (19), and mouse hippocampal neuronal cells (90) suggest targeted carbonylation of critical ER proteins, such as phosphate disulphide isomerase and calreticulin. Proteomic analysis of lysates from a rodent model of ALD confirms the susceptibility of chaperones HSP72, HSP90, and GRP78 to adduction by lipid alde-including in neurodegenerative disease (72,77,104,109), cerebral ischemia-reperfusion injury (77,110), cardiac ischemia-reperfusion injury (111)(112)(113), and in lymphocytes from aged humans (57,106). In-depth study of proteasome oxidation revealed that specific subunits are preferentially modified by reactive lipids and that, depending on which subunit is modified, catalytic activity of some, or all three, of the catalytic peptidase activities of the 20S proteasome can be inhibited (111,114,115).…”
Section: Lipotoxicity and Er Stressmentioning
confidence: 80%
See 3 more Smart Citations
“…In addition, proteomic analysis of lysates from aged murine liver (89), Alzheimer's disease brain (19), and mouse hippocampal neuronal cells (90) suggest targeted carbonylation of critical ER proteins, such as phosphate disulphide isomerase and calreticulin. Proteomic analysis of lysates from a rodent model of ALD confirms the susceptibility of chaperones HSP72, HSP90, and GRP78 to adduction by lipid alde-including in neurodegenerative disease (72,77,104,109), cerebral ischemia-reperfusion injury (77,110), cardiac ischemia-reperfusion injury (111)(112)(113), and in lymphocytes from aged humans (57,106). In-depth study of proteasome oxidation revealed that specific subunits are preferentially modified by reactive lipids and that, depending on which subunit is modified, catalytic activity of some, or all three, of the catalytic peptidase activities of the 20S proteasome can be inhibited (111,114,115).…”
Section: Lipotoxicity and Er Stressmentioning
confidence: 80%
“…As such, identification of specific modified proteins and a better understanding of how the modification affects protein function is a necessary step. To date, several large proteomics studies have aided our understanding of both the specificity and localization of protein carbonyls in tissue, such as adipose, liver, skeletal muscle, plasma, lung, and cardiac tissue (46,48,49,(57)(58)(59)(60)(61). Mass-spectrometry-based approaches have allowed for the identification of hundreds of direct targets of 4-HNE, 4-HHE, and acrolein carbonylation targets with cytosolic, mitochondrial, ER, and nuclear localization.…”
Section: Lipid Peroxidation and Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Research in our laboratory has pioneered global proteomic approaches to identify proteins that are post-translationally modified by reactive aldehydes in the liver. In recent murine and human studies in alcoholic liver disease we have identified 829 and 1244 proteins respectively that are carbonylated during conditions of increased hepatocellular stress 16,18 . In our current study, we utilized LC-MS/MS, immunohistochemistry and Western blotting to determine the impact of human end-stage fatty NASH and nonfatty NASH on protein carbonylation and anti-oxidant defense proteins.…”
Section: Introductionmentioning
confidence: 99%